Filipino parents' self-efficacy in managing anger and parental self-efficacy as predictors of parental rejection and child delinquency - Daganzo, Mary Angeline A. (Animo Repository, 2013)
The authors tested a model in which Filipino parents’ self-efficacy in managing anger/irritation influenced child delinquency via two parenting variables: parental self-efficacy and parental rejection. Structured interviews were conducted with 105 mothers and 83 fathers. Path analyses showed that for mothers, self-efficacy in managing anger/irritation negatively predicted child delinquency indirectly through the sequential mediation of parental self-efficacy and parental rejection. Mothers' self-efficacy in managing anger/irritation was also found to have a direct and negative relation to child delinquency. For father, self-efficacy in managing anger/irritation was indirectly and negatively related to child delinquency through it negative rejection only. Overall, results provided further evidence for the importance of efficacy beliefs, particularly self-efficacy in managing anger/irritation and parental self-efficacy, in the domain of child development.